Advantages of Cyanobacterial Bioactive-Compounds - Thummajitsakul, Sirikul (Journal of Advanced Development in Engineering and Science, 2023)
Cyanobacteria are photosynthetic prokaryote found commonly in natural resources, and are able to produce secondary metabolites such as photosynthetic pigments and self-defense biocompounds. These cyanobacterial biocompounds are variously applied in environments, foods, agricultures and medications for antimicrobial properties, antimultifunctional metabolisms, anticancer, antialgae bloom and used as insecticides.